The Relationship Between the Leadership Style of the Head of the Room and the Performance of Nurses in the Inpatient Room Ummi Rosnati Pertamedika Hospital - Nurromsyah Nasution; Siti Damayanti; Fitri Apriani (Journal of Nursing Management Innovations, 2025)
Background : Leadership style plays a crucial role in determining nurse performance, particularly in inpatient settings, which require high levels of cooperation, discipline, and motivation. The effectiveness of nursing services in hospitals is greatly influenced by how the ward manager leads their team. A leadership style that fails to foster motivation and support can hinder optimal performance.Aim : This study aims to determine the relationship between the leadership style of ward heads and the performance of nurses in the inpatient ward at Pertamedika Ummi Rosnati Hospital. The scope of the study includes identifying the dominant leadership style and its influence on nurses' behavior and work performance.Methods: This study employed a quantitative cross-sectional design using questionnaires distributed to inpatient nurses. Leadership style was measured with a validated instrument, and nurse performance was assessed using standard hospital performance indicators.Result: The study results showed that most nurses working under ward leaders with a democratic leadership style tended to have better performance. Analysis using the chi-square test showed a significant correlation (p < 0.039) between the ward leader's leadership style and nurse performance. These findings indicate that a democratic leadership style can improve nurse performance in terms of discipline, responsibility, teamwork, and high quality of service.Conclusion: There is a relationship between the ward head's leadership style and the performance of nurses. A communicative, supportive, and participatory leadership style can create a positive work environment and improve the quality of nursing services.